Sosialisasi Manajemen Pengelolaan Usaha Produktif bagi Pelaku UMKM di Desa Sempajaya, Kabupaten Karo - Elvin Desi Martauli; Frans Antoni Sihite; pakpahan, Yunita Eriyanti; Nurita Sembiring; Albert Jerico Sembiring Pandia; Harkendy Tarigan (EDUPEDIA Publisher, 2024)
Family welfare is very important in family life. The urgency in this community service is that family welfare will have a major impact on all aspects of life, such as family nutritional needs, economy, education, social, and other aspects. To ensure family welfare, various efforts are needed in accordance with the expertise of each individual who plays a role in a family. The purpose of the Community Service Activity is to provide Socialisation of Productive Business Management for MSMEs in Sempajaya Village, Karo Regency. The method of implementing the activity consists of three stages. First, the preparation stage includes pre-survey, team formation, PKM team coordination and village. The second stage is the program implementation stage in the form of socialisation. Socialisation was carried out through counselling (presentation of material) and discussion. The third stage is the evaluation and reporting stage. The evaluation was conducted by comparing the conditions of MSME actors before and after the implementation of the programme using interview and observation methods.